THE INTERTEXTUALITY BETWEEN “HOPE” BY EMILY DICKINSON AND “CAGED BIRD” BY MAYA ANGELOU - Rosid Humam (Universitas Islam Balitar, 2022)
This research is classified as descriptive qualitative research. The researcher took the theme of literature appreciation which refers to one type of literature, namely poems. The writer compared two poems, namely Emily Dickinson's